Evaluation of wild plants as lead (Pb) and cadmium (Cd) accumulators for phytoremediation of contaminated rice fields - Nuril Hidayati; Dwi Setyo Rini (Society for Indonesian Biodiversity, 2020)
Abstract. Hidayati N, Rini DS. 2020. Assessment of plants as lead and cadmium accumulators for phytoremediation of contaminated rice field. Biodiversitas 21: 1928-1934. Heavy metals contamination in agricultural land becoming a serious problem since this causes declining in agriculture production and quality and thus food safety. Meanwhile, conventional efforts for remediation of the contaminated agricultural lands have not been widely implemented due to high-cost constraints. A low-cost technology that can be applied in contaminated sites is phytoremediation. This technique is based on the fact that plants have the ability to extract and accumulate heavy metals. This research aimed to study the potentials of some plant species as accumulators for phytoremediation in rice fields contaminated by heavy metals of lead (Pb) and cadmium (Cd). Six selected accumulator plant species, namely Colocasia sp., Ipomoea fistulosa Mart. ex Choisy, Eichhornia crassipes (Mart.) Solms, Hymenachne amplexicaulis (Rudge) Nees), Saccharum spontaneum L., and Acorus calamus L., were tested in in-situ field to identify the performance of the plants as accumulators for Pb and Cd. Parameters observed were plant growth and biomass production, and the accumulation of Pb and Cd in plants which is formulated as: bioconcentration factor (BCF) to indicate concentration ratio of metal in plant to soil, and translocation factor (TF) to indicate metal transportation ratio of shoot to root. The results showed that plants with the highest growth rate under contaminated conditions were E. crassipes, A. calamus, and H. amplexicaulis. The highest value of BCF for Pb accumulation was recorded in the shoot of H. amplexicaulis and E. crassipes and in the root of H. amplexicaulis and A. calamus, whereas the highest value of TF for Pb was observed in E. crassipes, S. spontaneum, and H. amplexicaulis. Meanwhile, the highest value of BCF for Cd in the shoot and in the root was observed in Colocasia sp and H. amplexicaulis whereas the highest value of TF for Cd was identified in A calamus and Colocasia sp. With regards to the performance of plant growth, biomass production, and accumulation of Pb and Cd, it is suggested that three plant species, namely E. crassipes, A. calamus, and H. amplexicaulis are considered as potential Pb and Cd accumulators for phytoremediation of contaminated rice fields. Our findings suggest that some plants can produce high biomass and absorb high contaminants while other plants cannot, implying that plants respond differently to different environmental conditions. Therefore continuous research is required to obtain the best plant species for phytoremediation.